Relationship between participation and empowerment in women self help groups in Nigeria – a general analysis - Ndaeji, Muhammad Ndas; Abu Samah, Asnarulkhadi (Marsland Press, 2013)
In recent year, women’s empowerment through participation is said to be at the center stage in global development. The paper seeks to examine the relationship between participation in Self Help Group’s (SHG) activities and women empowerment in Nigeria. The participation of women in (SHGs) made a significant impact in social, economical and psychological aspects. Women empowerment through participation in SHG which is the focus of this paper is a process in which women are able to organize themselves to increase self-reliance and to assert their independent right to make choices in order to effectively promote their well being. The processes through which women achieve empowerment through participating in SHG is the essence of this article.